The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1111/ibi.12030
|View full text |Cite
|
Sign up to set email alerts
|

Corticosterone and stable isotopes in feathers predict egg size in Atlantic Puffins Fratercula arctica

Abstract: Examining factors that operate outside the breeding season may provide new insights into life‐history traits such as egg size, in which individual variation has not been fully explained. We measured corticosterone (CORT) levels and δ15N values (trophic level) in feathers grown several months before egg‐laying to test the prediction that a female's physiological state and feeding behaviour prior to the breeding season can influence egg mass in Atlantic Puffins Fratercula arctica. As predicted, egg mass increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
39
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 53 publications
(90 reference statements)
5
39
2
Order By: Relevance
“…Thus, egg-yolk corticosterone can serve as an integrated, non-invasive proxy of maternal physiology and may affect offspring development (Bowers et al 2015b). Moreover, conditions experienced prior to breeding are known to affect investment in eggs (Martin 1987; Nooker et al 2005; Ruffino et al 2012), and integrated measures of circulating corticosterone prior to the breeding season, as measured by corticosterone accumulated in feathers, recently have been found to predict egg size (Kouwenberg et al 2013), a trait that by itself has strong and persistent effects on offspring (Whittingham et al 2007; Krist 2011; Love and Williams 2011; Rollinson and Hutchings 2013; but see also Giordano et al 2014). However, effects of experimentally altered corticosterone levels within eggs on offspring development can be dynamic and context-dependent; for example, elevated corticosterone in eggs of the European starling ( Sturnus vulgaris ) can enhance the development of flight muscles after hatching and improve the flight performance of fledglings (Chin et al 2009), but also reduce the survival and growth of male offspring (Love et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, egg-yolk corticosterone can serve as an integrated, non-invasive proxy of maternal physiology and may affect offspring development (Bowers et al 2015b). Moreover, conditions experienced prior to breeding are known to affect investment in eggs (Martin 1987; Nooker et al 2005; Ruffino et al 2012), and integrated measures of circulating corticosterone prior to the breeding season, as measured by corticosterone accumulated in feathers, recently have been found to predict egg size (Kouwenberg et al 2013), a trait that by itself has strong and persistent effects on offspring (Whittingham et al 2007; Krist 2011; Love and Williams 2011; Rollinson and Hutchings 2013; but see also Giordano et al 2014). However, effects of experimentally altered corticosterone levels within eggs on offspring development can be dynamic and context-dependent; for example, elevated corticosterone in eggs of the European starling ( Sturnus vulgaris ) can enhance the development of flight muscles after hatching and improve the flight performance of fledglings (Chin et al 2009), but also reduce the survival and growth of male offspring (Love et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Bourgeon et al, 2014;Carbajal et al, 2014;Sepp et al, 2014) but these are in the minority. Concentrations of CORT in feathers have been shown to vary in response to life history events (Bortolotti et al, 2008;Crossin et al, 2013), sibling competition (Yosef et al, 2013), health status (Harriman et al, 2014;Meitern et al, 2013;Mougeot et al, 2010;Sild et al, 2014), overwinter survival (Koren et al, 2012), food limitation , reproductive investment (Fairhurst et al, 2012a;Kouwenberg et al, 2013), and with environmental conditions (Carrete et al, 2013;Fairhurst et al, 2011;Fairhurst et al, 2012b;Legagneux et al, 2013). Feather CORT concentrations have also been shown to be related to problem solving and learning (Bókony et al, 2014), and to feather pigmentation (Fairhurst et al, 2014;Kennedy et al, 2013;Lendvai et al, 2013;Martínez-Padilla et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Work with birds has shown that feathers contain corticosterone (CORT) (Bortolotti et al, 2008;Koren et al, 2012), the primary avian GC. CORT in feathers (CORT f ) has been correlated with variation in parental provisioning (Fairhurst et al, 2012b), nest box microclimate (Fairhurst et al, 2012a), environmental enrichment (Fairhurst et al, 2011), expression of carotenoid-based signals (Bortolotti et al, 2009b;Mougeot et al, 2010;Kennedy et al, 2013), egg mass (Kouwenberg et al, 2013), stable isotopes of carbon (Fairhurst et al, 2013) and components of fitness (Bortolotti et al, 2008;Koren et al, 2012). This biomarker relates to diverse ecological factors, suggesting that it integrates CORT secretion in general, rather than expresses a response to any specific source of environmental variation.…”
Section: Introductionmentioning
confidence: 99%